Effects of Aerobic Training on Resting Heart Rate among College Students - Irfan Ullah; Syed Sher Baz khan; Khalid Usman; Rahmat Gul*; Dr. Ashiq Muhammad (Al-Qanṭara, 2022)
There is an established link between aerobic training and resting heart rate. Reduced resting heart rate is an indication of fitness of an athlete because the athlete heart can meet the energy demand of the body with small number of beats. The purpose of the study was to investigate the effects of aerobic training on resting heart rate. The study was experimental in nature. The population of the study comprised of (male) students (18 to 22 years) of Government Post Graduate College Karak, Khyber Pakhtunkhwa (KP), Pakistan.The sample (n-50) of the study was determined through Physical Activity Readiness Questionnaire (PAR-Q). Before formation of two groups (Experimental and Control), the resting heart rate of each subject was taken by digital heart rate monitor. They were randomly divided into two equal groups of 25 each on the basis of their resting heart rate. The experimental group underwent aerobic training for eight weeks. There were four training sessions per week and each session comprised of 30 minutes. The subjects were offered aerobic exercises at moderate intensity (50% to 70% of the Maximum Heart Rate (MHR). The control group was allowed to participate in their daily routine life activities. After eight weeks aerobic training, the post test was conducted of both groups. The data were analyzed with the help of SPSS version 20 and used paired sample t test and independent sample t test as a statistical tool for a variable (resting heart rate) in order to determine the difference in means at <0.05 level. The mean values of pre-test and pos- test of each group were compared. The results of the study showed that there was significant decrease in resting heart rate of subjects of the experimental group, while there was no significant decrease in resting heart rate of subjects of the control group. In light of the findings of the study, it is concluded that aerobic exercises play important role in the reduction of resting heart rate. These qualities pave way to show good performance in endurance sports related activities among athletes. Key words: aerobic training, resting heart rate, college students